The Holy Quran | المصحف الشريف - Eliji | اليجي, Ali bin Sheikh Yassin | علي بن الشيخ يس (2023)
The black and red ink The font type is Levantine The resource type The beginning text of the manuscript In the name of God, the Most Merciful, the Most Merciful. The end of the manuscript, that is a nation that has passed, it has what it earned, and you have what you earned, and you are not questioned about what they used to do. The model is a picture of the endowment endowment of Ali bin Sheikh Yassin Al-Yaji, and the view of Sheikh Yassin Ibn Al-Sheikh Saeed in the month of Rajab 1311 AH. Decoration type Simple ornament and colorful frame. | المداد الأسود والأحمر نوع الخط مشرقي نوع المورد نص بداية المخطوط بسم الله الرحمن الرحيم، الحمد لله رب العالمين، الرحمن الرحيم. نهاية المخطوط تلك أمة قد خلت لها ما كسبت ولكم ما كسبتم ولا تسئلون عما كانوا يعملون. النموذج صورة الوقف وقف علي بن الشيخ يس اليجي، والنظر للشيخ ياسين ابن الشيخ سعيد في شهر رجب 1311 هجري. نوع التزيين زخرفة بسيطة وإطار ملون.